From monoculture to pluricultures: Recent trends in economics education - Lukas Bäuerle; Michelle Meixieira Groenewald (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2025)
The role of academic economics education in establishing and nurturing a monoculture of thought and action, emanating from this powerful discipline has been pivotal. However, as of today, there exists a vast array of pedagogical alternatives. These are contributing to an emerging pluriculture of future economics and future economies. The following chapter presents a framework to compare these pluralizing ambitions in (and of), economics education. Furthermore, we discuss in detail how recent trends in the debate are beginning to reflect economic education in the broader context of its socio-ecological pervasiveness. So too, we grapple with the process of reshaping it from an overtly imperialist tradition towards a decolonized and diversified domain, in terms of content, capabilities and didactics. Throughout the chapter we provide examples, databases and go-to manuals that have been established to foster pluralist economic education. This chapter does not diminish the challenges that exist in economics education but also seeks to point out instances where progress has been made, and offers avenues that exist for economic pluricultures to emerge.
Keywords: 330; Economic Education; Heterodox Economics; Pluralism; Social Studies of Economics